Diagnosis, treatment, and outcomes of encapsulated papillary carcinoma: a single institution experience - Steponavičienė, Laura; Gudavičienė, Daiva; Briedienė, Rūta; Petroška, Donatas; Garnelytė, Aušra (Acta medica Lituanica, 2018)
Background. Encapsulated papillary carcinoma (EPC) is a rare entity of breast cancer accounting for approximately 1–2% of all breast tumours. There are no evidence-based guidelines for the treatment of EPC. Materials and methods. From the database of the National Centre of Pathology (NCP), we obtained pathology reports of 19 patients with histologically confirmed EPC, who were treated at the National Cancer Institute (NCI) in Vilnius, Lithuania, between July 2009 and July 2015. Demographic, diagnostic and treatment data were collected from medical records retrospectively. Results. During the indicated period, 19 patients with EPC were treated at the NCI. Three of them had pure EPC, they were 74 to 81 years of age at the time of diagnosis (mean 76.7 years, median 75 years); all of them are still alive and no disease progression has been observed. Seven patients had EPC associated with carcinoma in situ. Nine patients had EPC associated with invasive breast ductal carcinoma. All patients underwent surgery, in most cases – wide local excision. Only one patient died. Conclusions. EPC is a rare form of breast cancer and usually presents with an invasive breast carcinoma or carcinoma in situ in postmenopausal women. Tumours have an excellent prognosis in the cases of pure EPC and in both EPC associated with carcinoma in situ (CIS) and invasive carcinoma.